Small habitat matrix: How does it work? - Casey Keat-Chuan Ng; John Payne; Felicity Oram (2020)
We present herein our perspective of a novel Small Habitats Matrix (SHM) concept showing how small habitats on private lands are untapped but can be valuable for mitigating ecological degradation. Grounded by the realities in Sabah, Malaysian Borneo, we model a discontinuous “stepping stones” linkage that includes both terrestrial and aquatic habitats to illustrate exactly how the SHM can be deployed. Taken together, the SHM is expected to optimize the meta-population vitality in monoculture landscapes for aerial, arboreal, terrestrial and aquatic wildlife communities. We also provide the tangible cost estimates and discuss how such a concept is both economically affordable and plausible to complement global conservation initiatives. By proposing a practical approach to conservation in the rapidly developing tropics, we present a perspective from “ground zero” that reaches out to fellow scientists, funders, activists and pro-environmental land owners who often ask, “What more can we do?”